2020
DOI: 10.1111/cea.13769
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with rhinitis, allergic conjunctivitis and eczema among schoolchildren in Uganda

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
0
9
0
6
Order By: Relevance
“…In the present study, dampness or mildew at home was an independent risk factor, with aORs of 1.50 and 1.63 for ever asthma and current asthma, respectively, in line with previous studies in recent years ( 31 , 32 ). A recent case–control study in Uganda has demonstrated that schoolchildren who lived in areas with frequent truck traffic were 2.59-fold more likely to have asthma symptoms ( 33 ). It is generally accepted that tobacco smoke and particle pollution facilitate allergic sensitization to common allergens and increase the tendency of allergy ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, dampness or mildew at home was an independent risk factor, with aORs of 1.50 and 1.63 for ever asthma and current asthma, respectively, in line with previous studies in recent years ( 31 , 32 ). A recent case–control study in Uganda has demonstrated that schoolchildren who lived in areas with frequent truck traffic were 2.59-fold more likely to have asthma symptoms ( 33 ). It is generally accepted that tobacco smoke and particle pollution facilitate allergic sensitization to common allergens and increase the tendency of allergy ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A community‐based study in Ghana reported a 39.9% prevalence of allergic conjunctivitis in school‐going children 55 . The prevalence of allergic conjunctivitis is also relatively high in other regions of Africa (e.g., 32% in Nigeria, 56 39.5% in Uganda, 57 37.2% in Mali 58 and 11.10% in Ethiopia 59 ) compared with lower prevalence rates in Europe (e.g., Italy 2.4%–27.8%, Finland 0.7%–8.4%, Sweden 1.2%–8.7%, The Netherlands 0.6%–4.6%, France 0.7%–3.3% and Norway 0.3%–1.9%) 60 . Although, there is no solid consensus in the literature, some investigations have reported a significant association between atopy and keratoconus 9,61 …”
Section: Discussionmentioning
confidence: 99%
“…These chronic recurrent conditions cause significant physical and psychological distress, sleep disturbance and reduced quality of life among patients of all ages [10]. Often, patients with ocular allergies have coexisting atopic manifestations such as rhinitis, asthma, urticaria, or eczema [11,12]. In multicenter studies such as the International Study of Asthma and Allergies in Childhood (ISAAC) [12,13] and the National Health And Nutrition Examination Survey (NHANES) [14], the association of allergic conjunctivitis was demonstrated above all with respiratory diseases such as rhinitis, followed by asthma and finally eczema [10,15].…”
Section: Discussionmentioning
confidence: 99%